Chromaffin granule-associated phosphatidylinositol 4-kinase activity is required for stimulated secretion. - Wiedemann, C (1996)
Permeabilized bovine adrenal chromaffin cells have been used to characterize the MgATP requirement of processes preceding exocytosis. Incubation of primary cultures with the membrane-permeable phenylarsine oxide (PAO) at 20 microM inhibited the phosphorylation of phosphatidylinositol (PtdIns) and completely blocked secretion. This block could be reversed by addition of 2,3-dimercaptopropanol to the permeabilized cells. Simultaneous addition of [gamma32P]ATP and 2,3-dimercaptopropanol permitted a comparison between recovery of secretion and phosphorylation of intracellular components. Recovery of secretion closely correlated with phosphorylation of PtdIns and PtdIns4P. Subcellular fractionation of permeabilized cells after recovery of secretion revealed that the majority of newly phosphorylated PtdIns4P was localized on the chromaffin granules. In accordance with these results, PtdIns 4-kinase activity was found in protein extracts of permeabilized cells as well as associated with purified chromaffin granules, sensitive in both cases to PAO. Additionally, PtdIns 4-kinase activity in these two assays was inhibited by quercetin. In permeabilized cells, quercetin decreased the levels of labeled PtdIns4P and Ptdlns(4,5)P2 and inhibited secretion. Our data suggest that a chromaffin granule-associated PtdIns 4-kinase acts in the priming of exocytosis.